Existence of the solution to electromagnetic wave scattering problem for an impedance body of an arbitrary shape. (March 2015) - Ramm, Alexander G.; Schechter, Martin
Abstract: A new proof is given for the existence of the solution to electromagnetic (EM) wave scattering problem for an impedance body of an arbitrary shape. The proof is based on the elliptic systems theory and elliptic estimates for the solutions of such systems.